1973
DOI: 10.1111/j.1399-0039.1973.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Lymphocytotoxic Anti‐Human Antibodies in Normal Rabbit Sera

Abstract: Forty‐nine of 127 normal sera from New Zealand white rabbits were found to contain cytotoxic antibodies against human lymphocytes. Reactions with these sera did not correlate with those of known HL–A or ABO specificities. However, four distinct specificities were found in 18 sera. These antibodies are labile upon prolonged storage at −20°C and heating at 56°C for 30 min and have low avidity. Since rabbit serum is the most efficient source of complement in the cytotoxic reaction with human lymphocytes, the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Rabbits' natural antibodies to human lymphocyte antigens are mainly IgM in nature, activate the classical pathway of the complement system (Ferrone et al 1974a) and are directed to a human polymorphic antigenic system which is distinct from other cell surface markers (Mittal et a! .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbits' natural antibodies to human lymphocyte antigens are mainly IgM in nature, activate the classical pathway of the complement system (Ferrone et al 1974a) and are directed to a human polymorphic antigenic system which is distinct from other cell surface markers (Mittal et a! .…”
mentioning
confidence: 99%
“…2) Density and spatial relationship of HLA antigens with lymphocyte antigens reacting with natural rabbit antibodies. Discordant reactions of normal rabbit sera with lymphocytes from HLA identical siblings have suggested that lymphocyte antigens segregate independently from HLA antigens (Mittal et al 1973), but no data are available on the spatial relationship between various HLA specificities on lymphocyte membranes and antigens that react with natural rabbit antibodies. Points 1 and 2 may explain why not all the sera defining a given HLA specificity give unexpected reactions with a panel of human peripheral lymphocytes.…”
mentioning
confidence: 99%